Fatigue strength of additively manufactured 316L austenitic stainless steel. (15th October 2020) - Kumar, Punit; Jayaraj, R.; Suryawanshi, J.; Satwik, U.R.; McKinnell, J.; Ramamurty, U.
Abstract: The microstructures and mechanical properties of the 316L austenitic stainless steel fabricated using binder jet printing (BJP) and selective laser melting (SLM) were investigated and compared with those of the conventionally manufactured (CM) alloy, with particular emphasis on the unnotched fatigue resistance. Results show that the work hardening behavior, ductility, and fatigue strength ( σ f ) of the BJP specimens, which contain significant amounts of pores, are surprisingly comparable to those of the CM alloy. In contrast, the SLM specimens are considerably stronger, especially in terms of the yield strength, less ductile, and far inferior in terms of σ f although the porosity in them is relatively smaller as compared to the BJP specimens. These results are rationalized by recourse to the distinct microstructures in the two additively manufactured alloys, which stem from the different processing conditions experienced by them. The planar slip regime that prevails in the early stages of plastic deformation of the BJP alloys and a combination of other microstructural factors lead to the arrest of small cracks that nucleate at the corners of the pores, both under quasi-static and cyclic loads; as a result, neither ductility nor fatigue strength are adversely affected by the porosity in the BJP alloys. In the SLM alloy, the cellular structure, which enhances the yield strength considerably, is too fine whereas the columnar grains are minimally misoriented and coarse enough to induce any crack deflection or arrest. Implications of these results in terms of possible directions for designing AM alloys with high mechanical performance are discussed. Graphical abstract: Image, graphical abstract